2002
DOI: 10.1111/1475-4983.00277
|View full text |Cite
|
Sign up to set email alerts
|

Poekilopleuron bucklandii, the theropod dinosaur from the Middle Jurassic (Bathonian) of Normandy

Abstract: ABSTRACT. Poekilopleuron bucklandii, described by Eudes-Deslongchamps in 1838, is one of the earliest discovered dinosaurs. Although incomplete, it is one of the best preserved Middle Jurassic theropods known from Europe. Unfortunately, the only specimen of P. bucklandii, housed in the Muse Âe de la Faculte  des Sciences de Caen, was destroyed during World War II. However, casts of some parts of the type skeleton have been found in the collections of the Museum National d'Histoire Naturelle, Paris. These cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 13 publications
3
55
0
7
Order By: Relevance
“…Allain and Chure (2002), however, proposed that multiple taxa were represented in the large theropod material from the Stonesfield Slate, an observation confirmed by Day and Barrett (2004). It was suggested that the taxon should be restricted to the lectotype dentary (OUMNH J.13505) and it was recommended that Megalosaurus , as formerly considered, should not be included in cladistic analyses as such analyses would be utilising a chimera (Allain and Chure, 2002). The latter authors also failed to find diagnostic features of the dentary and thus considered Megalosaurus to be a nomen dubium .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Allain and Chure (2002), however, proposed that multiple taxa were represented in the large theropod material from the Stonesfield Slate, an observation confirmed by Day and Barrett (2004). It was suggested that the taxon should be restricted to the lectotype dentary (OUMNH J.13505) and it was recommended that Megalosaurus , as formerly considered, should not be included in cladistic analyses as such analyses would be utilising a chimera (Allain and Chure, 2002). The latter authors also failed to find diagnostic features of the dentary and thus considered Megalosaurus to be a nomen dubium .…”
mentioning
confidence: 99%
“…(1990) formally proposed designation of the dentary (OUMNH J.13505) as the lectotype, rendering the rest of the syntype series paralectotypes. However, as none of the paralectotypes can be convincingly referred to the same taxon as the lectotype dentary we follow Allain and Chure (2002) in restricting the hypodigm of Megalosaurus bucklandii to the lectotype pending the discovery of additional comparable material.…”
mentioning
confidence: 99%
“…All of these remains have been assigned to tetanurans (Allain & Chure, 2002;Holtz, Molnar & Currie, 2004), and confirmed non-tetanuran theropods from the Middle Jurassic are unknown (Tykoski & Rowe, 2004;Carrano & Sampson, 2008; but see Rauhut, 2005b). All of the taxa represented by this material have been recovered as members of Tetanurae by numerous phylogenetic analyses (Allain, 2002;Rauhut, 2003;Holtz, Molnar & Currie, 2004).…”
Section: A Comparison Of Monolophosaurus With Other Middle Jurassimentioning
confidence: 62%
“…Distal to that, the groove is deeper than in the proximal part. Incomplete fibula of Poekilopleuron also bears a concavity on its medial surface that seems to flatten more distally (Eudes-Deslongchamps 1838; Allain & Chure 2002). Anteroposterior expansion of the proximal part of fibula of Baryonyx seems to be much broader anteroposteriorly than in Velocipes.…”
Section: Basal Theropods and Problematic Saurischiansmentioning
confidence: 99%